2004
DOI: 10.1002/jemt.20050
|View full text |Cite
|
Sign up to set email alerts
|

The physiology of insect auditory afferents

Abstract: This review presents an overview of the physiology of primary receptors serving tympanal hearing in insects. Auditory receptor responses vary with frequency, intensity, and temporal characteristics of sound stimuli. Various insect species exploit each of these parameters to differing degrees in the neural coding of auditory information, depending on the nature of the relevant stimuli. Frequency analysis depends on selective tuning in individual auditory receptors. In those insect groups that have individually … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 131 publications
(139 reference statements)
0
21
0
1
Order By: Relevance
“…The temporal profile of the population response of the auditory nerve has been shown to be invariant for the same speech utterance under voiced and whispered conditions (Stevens and Wickesberg, 1999). In insects, auditory receptors respond synchronously at the onsets of temporally distinct sounds, producing a neural population response that faithfully mimics the basic temporal pattern of the stimulus (Mason and Faure, 2004). Machens et al (2001) found that using the population response of grasshoppers' auditory receptors increased the accuracy of temporal encoding over single responses such that the neural sensitivity to temporal information approached behavioral levels.…”
Section: Stimulus-dependent Tuning Population Coding and Ensemble Smentioning
confidence: 99%
See 1 more Smart Citation
“…The temporal profile of the population response of the auditory nerve has been shown to be invariant for the same speech utterance under voiced and whispered conditions (Stevens and Wickesberg, 1999). In insects, auditory receptors respond synchronously at the onsets of temporally distinct sounds, producing a neural population response that faithfully mimics the basic temporal pattern of the stimulus (Mason and Faure, 2004). Machens et al (2001) found that using the population response of grasshoppers' auditory receptors increased the accuracy of temporal encoding over single responses such that the neural sensitivity to temporal information approached behavioral levels.…”
Section: Stimulus-dependent Tuning Population Coding and Ensemble Smentioning
confidence: 99%
“…Other acoustic communication signals that may be less rich in the spectral domain are highly temporally structured (Suga, 1989;Bass and McKibben, 2003;Kelley, 2004;Mason and Faure, 2004). Correspondingly, behavioral and physiological studies suggest a strong relationship between the accurate perception of communication sounds and temporal auditory processing (Tallal et al, 1993;Shannon et al, 1995;McAnally and Stein, 1996;Wright et al, 1997;Woolley and Rubel, 1999;Escabi et al, 2003;Marsat and Pollack, 2005;.…”
Section: Introductionmentioning
confidence: 99%
“…Several mechanisms have been identified by which acoustic parameters may be represented in receptor responses, including temporal coding for directional information. Directional sound sources generate intensity differences at the two ears, so that interaural differences in response rate or latency, or both, could encode directional information (Mason and Faure, 2004). With the exception of the fly Ormia ochracea (the eardrums are mechanically coupled), pressure difference reception has become the standard explanation for directionality in small animals (Michelsen and Larsen, 2008).…”
Section: Research Articlementioning
confidence: 99%
“…Seus órgãos auditivos podem variar desde um sensilo tátil até órgãos timpânicos mais complexos, formados por uma estrutura especializada (Lara 1979). Mason & Faure (2004) estudaram a fisiologia de receptores auditivos em insetos e observaram que eles respondem a diferentes estímulos sonoros e são capazes de detectar uma ampla gama de sinais acústicos transmitidos através do ar, água e sólidos. Yack (2004), revendo as especializações do órgão cordotonal em insetos, ressalta que pouco se conhece sobre os mecanismos de transdução e captação do som utilizados pelos mesmos.…”
unclassified